2021
DOI: 10.2147/cia.s295524
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD in the Elderly

Abstract: Non-alcoholic fatty liver disease (NAFLD) is an increasingly prevalent disease globally. Current estimates are that 24% of the adult population, thus, one billion individuals worldwide, are affected. Interestingly, the prevalence of fatty liver seems to peak between 40─50 years of age in males and 60─69 years in females, often slightly decreasing in older (>70 years) cohorts. Furthermore, several risk factors for NAFLD development, such as hypertension, diabetes, hyperlipidemia, and obesity are higher in older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 160 publications
(193 reference statements)
2
32
0
2
Order By: Relevance
“…Multiple risk factors including type 2 diabetes, obesity, and hyperinsulinemia predispose for the development and progression of NAFLD [ 1 ]. As people age, they become more vulnerable to these risk factors, which can be explained in part at the cellular level by the increased senescence [ 19 ]. Thus, cellular senescence represents a potential target of ageing- and metabolic-related diseases [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors including type 2 diabetes, obesity, and hyperinsulinemia predispose for the development and progression of NAFLD [ 1 ]. As people age, they become more vulnerable to these risk factors, which can be explained in part at the cellular level by the increased senescence [ 19 ]. Thus, cellular senescence represents a potential target of ageing- and metabolic-related diseases [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with ART and HIV infection is known to be pro-steatogenic with worse metabolic outcomes-dependent on the chosen ART regimen [9,10]. Nevertheless, an increasingly sedentary lifestyle with poor dietary and physical habits and a higher age impose an additional threat to the metabolic health of PLWH [11]. These factors have also led to a rise in the prevalence of hepatic steatosis, negatively impacting the HRQL in PLWH [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…By combining Targher's results and this study, it is suggested that the prevalence of NAFLD increases with age until about 60 years (as in Targher's study) and then decreases with age, as shown in this study. An "inverted U curve," in which the prevalence of NAFLD reaches a peak in late adulthood and decreases afterward has been reported in the general population[ 27 - 29 ]. However, a meta-analysis observed a consistent increase in the NAFLD prevalence across all age groups[ 30 ].…”
Section: Discussionmentioning
confidence: 99%